Behaviour of Precast Beam to Column Connection under Seismic Loading - Nepesov, Parahat (IRC, 2019)
This work is intended to study behaviour of precast beam to column connection under seismic loading. Most of the studies reported on precast beam-column joints are showing that they tend to behave poorly in regions high seismic activities. It has been recognized that the weakest part of a precast structure is the connection, more particularly beam to column connection. To conduct physical test on this, tends to be uneconomic, therefore number of numerical model studies to be done and to understand the precast beam column connection behaviour. ANSYS will be used to conduct numerical experiments. The model of precast beam to column connection will be designed depending on desired shapes. For the seismic loading, lateral load will be applied on the connection. The behaviour of beam-column connection will be observed, examined and analysed.